Imaging in forensic science: Five years on - Carew, Rachael M.; Errickson, David (Cranfield University, 2019)
The Journal of Forensic Radiology and Imaging was launched in 2013 with the aim to collate the literature and demonstrate high-quality case studies on image-based modalities across the forensic sciences. Largely, the focus of this journal has been on the transmissive aspect of forensic imaging, and therefore a significant number of high-quality case studies have been published focusing on computed tomography and magnetic resonance imaging. As a result, the ‘and imaging’ aspect is often neglected. Since 2013, technology has fundamentally evolved, and a number of new techniques have become accessible or have been demonstrated as particularly useful within many sub-disciplines of forensic science. These include active and passive surface scanning techniques, and the availability of three-dimensional printing. Therefore, this article discusses non-contact techniques, their applications, advantages, and considerations on the current state of play of imaging in forensic science.
Keywords: Imaging; Three-dimension; Evidence; Visualisation; Non-Contact; Courtroom; Ethics; Bias; Data